The role of artistic art exhibitions in public spaces in The city of Machala - Nuñez Cevallos, Manuel Sebastián; Romero Espinoza, Lenin Efraín; Benítez Narváez, Robinson Miguel (SATHIRI, 2023)
The purpose of this research is to analyze the art exhibitions in the public places of a town. The research approach is mixed, of a non-experimental nature and of a bibliographic, descriptive and field type. To obtain the information, a survey was applied, consolidated in a questionnaire of five questions, to the entire population of the members of the board of directors of the House of Culture and the Subdirectorate of Culture of the municipality ofMachala. The data collected allows us to conclude that 76.47% maintain that the Machala Mayor’s Office has not requested the development of an exhibition plan for artistic art inpublic spaces; 82.35% (some agree and disagree, as well), ratify that they have the conditions to hold an event on the living arts. 88.24% expresses that the directory does not have a specificbudget for the events in question. 82.35% confirms that they do not have the technical and human logistics to carry out artistic art exhibitions in public spaces. 70.59% states that there is a great acceptance by the citizens of Machala for these programs. This denotes, on the need for generate cultural policies that guide the actions of the main representative of the Mayor’sOffice of Machala, the House of Culture and the Subdirectorate of Culture of the municipality, on the need to increase artistic expression events in different public places within Machalafolk context, this will allow both individually and collectively people may have presentationsin public.